Profil dan Sikap Politik Perempuan Anggota DPRD di Sumbar Pasca Kuota 30% Keterwakilan Perempuan dalam Pencalonan Anggota Legislatif - Rafni, Al (Jurnal Demokrasi, 2008)
This study tried to explain about the profile women legislator after the quota of 30% women representation in legislator recruitment and their political efficacy toward political system in West Sumatera. The data is collected from 15 respondents of women legislator. Data in this study was collected through questionnaire and analyzed by using quantitative descriptive method. Data was also collected through deep interview and analyzed by using interactive model analysis. The finding of this research indicated that there are variations in their level of education and generally it seemed that their qualifications were good enough, while their efficacy toward political system are very positive. Kata Kunci: Profil, sikap politik, keterwakilan, perempuan, legislatif